2018
DOI: 10.2147/ndt.s169940
|View full text |Cite
|
Sign up to set email alerts
|

The microglial activation profile and associated factors after experimental spinal cord injury in rats

Abstract: BackgroundSpinal cord injury (SCI) has imposed a great impact on the quality of life of patients due to its relatively young age of onset. The pathophysiology of SCI has been proven to be complicated. Microglia plays an important role in neuroinflammation and second injuries after SCI. Different environment and other factors may determine the microglial activation profile and what role they play. However, neither accurate time-course profiles of microglial activation nor influence factors have been demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
(51 reference statements)
2
16
0
Order By: Relevance
“…Pathological changes between CA and ROSC may be related to the degree of neurological dysfunction. Microglia, resident immune cells in the central nervous system (CNS), are increased in number and morphologically activated at an early stage after spinal cord injury [35,36], which contributes to neuroinflammation and onset of neuronal damage by releasing large amount of inflammatory cytokines and ROS [37,38]. Similar to previous studies, our results showed that ACA resulted in significant microglia activation in the ventral horn of the lumbar spinal cord.…”
Section: Discussionsupporting
confidence: 85%
“…Pathological changes between CA and ROSC may be related to the degree of neurological dysfunction. Microglia, resident immune cells in the central nervous system (CNS), are increased in number and morphologically activated at an early stage after spinal cord injury [35,36], which contributes to neuroinflammation and onset of neuronal damage by releasing large amount of inflammatory cytokines and ROS [37,38]. Similar to previous studies, our results showed that ACA resulted in significant microglia activation in the ventral horn of the lumbar spinal cord.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, microglia are activated and together with the infiltrating monocytes/macrophages into the injured site release a panel of cytokines, such as TNF-α, IL-1β, and IL-1α, which further worsen the local environment and contribute to a massive damage of the surrounding tissue. [19,20] Other events like ischemia, glutamate excitotoxicity, and apoptosis contribute to the formation of the glial scar that is surrounded by reactive astrocytes, creating an inhibitory microenvironment for axonal regrowth or tissue regeneration. [21] Until today there is no effective treatment to tackle SCI.…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…The functions of the immune system change significantly as the immediate post-traumatic phase after the injury progresses to a chronic phase. The loss or dysfunction of vegetative innervation in the lymphatic and endocrine tissues causes immune response disorders that last quite a long time after the initial trauma [ 84 ]. The main manifestations of such disorders are immune depression and the autoimmune process [ 83 ], although inflammatory reactions also remain pathogenetically significant.…”
Section: The Immune and Cytokine Processes Accompanying The Chronimentioning
confidence: 99%